SPORTIVE PEDAGOGY AND POLE DANCE EDUCATION IN SCHOOL: AN ACTION RESEARCH ON IMPACTS IN THE LESSONS OF PHYSICAL EDUCATION - Rizzo, Deyvid Tenner de Souza; Golin, Carlo Henrique; Sousa, Ana Paula Moreira de; Aranha, Ágata Cristina Marques (Cadernos de Educação Tecnologia e Sociedade, 2020)
The present study is qualitative, interventional and action research, which seeks to discuss the concepts and practice of Pole Dancesport at school. The main objective was to develop and propose a pedagogical possibility for the learning of this sport in the school based on the interactionist theory, considering that there are no "models" in force today. It also aims to know the impacts of learning caused on the students involved with the proposal of the practice of Pole Dance. We believe that the pedagogy of teaching Pole Dance in school must be based on different dimensions as the content of school physical education, especially conceptual, procedural and attitudinal. In this way, we understand that this content can also be developed in the context of Physical Education at school, bringing cultural, social and motor benefits to the students involved in the proposal. We emphasize that Pole Dance is something different to be developed pedagogically in schools, even recognized today as a manifestation (sport), even considered by many still as something atypical and unusual in Physical Education.